Contrasting arsenic cycling in strongly and weakly stratified contaminated lakes: Evidence for temperature control on sediment–water arsenic fluxes. (28th January 2019) - Barrett, P. M.; Hull, E. A.; Burkart, K.; Hargrave, O.; McLean, J.; Taylor, V. F.; Jackson, B. P.; Gawel, J. E.; Neumann, R. B.
Abstract: Arsenic contamination of lakebed sediments is widespread due to a range of human activities, including herbicide application, waste disposal, mining, and smelter operations. The threat to aquatic ecosystems and human health is dependent on the degree of mobilization from sediments into overlying water columns and exposure of aquatic organisms. We undertook a mechanistic investigation of arsenic cycling in two impacted lakes within the Puget Sound region, a shallow weakly stratified lake and a deep seasonally stratified lake, with similar levels of lakebed arsenic contamination. We found that the processes that cycle arsenic between sediments and the water column differed greatly in shallow and deep lakes. In the shallow lake, seasonal temperature increases at the lakebed surface resulted in high porewater arsenic concentrations that drove larger diffusive fluxes of arsenic across the sediment–water interface compared to the deep, stratified lake where the lakebed remained 10°C cooler. Plankton in the shallow lake accumulated up to an order of magnitude more arsenic than plankton in the deep lake due to elevated aqueous arsenic concentrations in oxygenated waters and low phosphate : arsenate ratios in the shallow lake. As a result, strong arsenic mobilization from sediments in the shallow lake was countered by large arsenic sedimentation rates out of the water column driven by plankton settling.